The Church: Towards a Shared Vision: A Contribution from Pentecostalism - Salazar-Sanzana, Elizabeth (Exchange, 2015)
Pentecostalism has taken its own diverse paths, also with regard to its relation with the ecumenical movement. However, most of the Pentecostal movement has developed with an aversion to ecumenism. This reflection considers its limitations, because of the diversity of Pentecostalism and because of the fact that the written theological reflection is very much dissociated from the everyday practices of communities. One must consider the fragility of the ecumenical movement against the Pentecostal versatility. In Pentecostalism, the church as the body of Christ in unity and communion is understood as centred in the gospel, guided at all times by Christ himself as path, truth and life. This is where we can find points of convergence with the ctcv document. This contribution comes from an optimistic conviction about ecumenism, in resonance with this process of dialogue and other reflections for strengthening the church and its witness.